BANTUAN-BANTUAN YANG DIBERIKAN ISLAMIC RELIEF WORLDWIDE BAGI KORBAN KONFLIK SURIAH - Mir'atunnnisa (HI 16 UMY, 2016)
The most important part of this paper is analyze the role of Islamic Relief Worldwide as a humanitarian NGO which provides and gives aid in Syria’s conflict during 2011 to 2015. The aids provided by Islamic Relief Worldwide is given both directly and indirectly especially for the refugees in Syria as well as in other countries. The aids are given by mobilizing and executing cooperation with other local and international humanitarian organization. Further, another important thing discussed in this paper is about the obstacles which Islamic Relief Worldwide has to face during the aid distribution in Syria. To explain the main topic in this paper, the researcher used the concepts of humanitarian action and NGO mobilization.